Optimizing Outcomes in Cardiac Rehabilitation: The Importance of Exercise Intensity - Taylor, Jenna L.; Bonikowske, Amanda R.; Olson, Thomas P. (Frontiers in Cardiovascular Medicine, 2021)
Exercise based cardiac rehabilitation (CR) is recognized internationally as a class 1 clinical practice recommendation for patients with select cardiovascular diseases and heart failure with reduced ejection fraction. Over the past decade, several meta-analyses have generated debate regarding the effectiveness of exercise-based CR for reducing all-cause and cardiovascular mortality. A common theme highlighted in these meta-analyses is the heterogeneity and/or lack of detail regarding exercise prescription methodology within CR programs. Currently there is no international consensus on exercise prescription for CR, and exercise intensity recommendations vary considerably between countries from light-moderate intensity to moderate intensity to moderate-vigorous intensity. As cardiorespiratory fitness (peak oxygen uptake (VO2peak)) is a strong predictor of mortality in patients with coronary heart disease and heart failure, exercise prescription that optimizes improvement in cardiorespiratory fitness and exercise capacity is a critical consideration for the efficacy of CR programming. This review will examine the evidence for prescribing higher-intensity aerobic exercise in CR, including the role of high-intensity interval training. This discussion will highlight the beneficial physiological adaptations to pulmonary, cardiac, vascular, and skeletal muscle systems associated with moderate-vigorous exercise training in patients with coronary heart disease and heart failure. Moreover, this review will propose how varying interval exercise protocols (such as short-duration or long-duration interval training) and exercise progression models may influence central and peripheral physiological adaptations. Importantly, a key focus of this review is to provide clinically-relevant recommendations and strategies to optimize prescription of exercise intensity while maximizing safety in patients attending CR programs.